Risk of new-onset long COVID following reinfection with SARS-CoV-2: community-based cohort study - Bosworth, ML; Shenhuy, B; Walker, AS; Nafilyan, V; Alwan, NA; O'Hara, ME; Ayoubkhani, D (Oxford University Press, 2023)
Background Little is known about the risk of long COVID following reinfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We estimated the likelihood of new-onset, self-reported long COVID after a second SARS-CoV-2 infection, compared to a first infection.